HIV Vpu Interferes with NF-κB Activity but Not with Interferon Regulatory Factor 3 - Manganaro, Lara (J Virol, 2015)
The accessory HIV protein Vpu inhibits a number of cellular pathways that trigger host innate restriction mechanisms. HIV Vpu-mediated degradation of tetherin allows efficient particle release and hampers the activation of the NF-κB pathway thereby limiting the expression of proinflammatory genes. In addition, Vpu reduces cell surface expression of several cellular molecules such as newly synthesized CD4. However, the role of HIV Vpu in regulating the type 1 interferon response to viral infection by degradation of the interferon regulatory factor 3 (IRF3) has been subject of conflicting reports. We therefore systematically investigated the expression of IRF3 in primary CD4(+) T cells and macrophages infected with HIV at different time points. In addition, we also tested the ability of Vpu to interfere with innate immune signaling pathways such as the NF-κB and the IRF3 pathways. We report here that HIV Vpu failed to degrade IRF3 in infected primary cells. Moreover, we observed that HIV NL4.3 Vpu had no effect on IRF3-dependent gene expression in reporter assays. On the other hand, HIV NL4.3 Vpu downmodulated NF-κB-dependent transcription. Mutation of two serines (positions 52 and 56) involved in the binding of NL4.3 Vpu to the βTrCP ubiquitin ligase abolishes its ability to inhibit NF-κB activity. Taken together, these results suggest that HIV Vpu regulates antiviral innate response in primary human cells by acting specifically on the NF-κB pathway. IMPORTANCE HIV Vpu plays a pivotal role in enhancing HIV infection by counteraction of Tetherin. However, Vpu also regulates host response to HIV infection by hampering the type 1 interferon response. The molecular mechanism by which Vpu inhibits the interferon response is still controversial. Here we report that Vpu affects interferon expression by inhibiting NF-κB activity without affecting IRF3 levels or activity. These data suggest that Vpu facilitates HIV infection by regulating NF-κB transcription to levels sufficient for viral transcription while limiting cellular responses to infection.